The transition of Southeastern European societies towards civil democracy and market economy: problems and perspectives - Miltiades Kipas (Cahiers Balkaniques)
After the collapse of the centrally planned economies in Southeastern Europe, the new governments that came to power tried to create institutions capable of meeting the needs of new era and the imperatives of the neoliberal economy. They had to face the nationalist logic that penetrated the Balkan populations, similar to that of other parts of the world, such as Africa and Asia, or even in Europe such as Catalonia or the Basque struggle. A special study is required to understand the problems that have arisen in the Balkan region, such as population shifts, urban modernization after four decades of “existing socialism” with the particular characteristics of that era. It is also important to analyze the major socioeconomic developments that have taken place in the Balkan countries since 1989.